Using an Accountability Tool to Improve the Quality of Outcomes on Individual Family Service Plans - Votava, Kristen M.; Johnson, Carol; Chiasson, Kari (Journal of the American Academy of Special Education Professionals, 2011)
This study investigated using a state’s Part C early intervention accountability tool to increase the number of outcomes meeting compliance within IFSPs. The Case Review Tool (CRT) was used to examine differences from year one to year three on three measures of quality outcomes. There was no evidence of change in two of the measures, but there was evidence that IFSP outcomes increased in the components of functional and measureable after three years of using the CRT. There was also an increase in the number of outcomes from year one to year three.